2010
DOI: 10.1159/000303057
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Cell-cell Contacts during Intestinal Restitution <i>In Vitro</i> and Effects of Epidermal Growth Factor (EGF)

Abstract: Mucous epithelia represent a major barrier to the outside world and are capable of undergoing rapid repair after injury by cell migration, a process called “restitution”. Here, a sensitive RT-PCR method was applied allowing systematic gene expression analysis of separated stationary and migratory non-transformed IEC-18 and IEC-6 cells after scratch wounding. The focus was on genes related to cell-cell contacts. Furthermore, the effect of epidermal growth factor (EGF) on gene expression was studied. Most of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Reducing expression of cell junction genes led to increased paracellular permeability. A previous study reported that several cell junction genes were modulated by EGF, 15) so we tested whether simotinib increased the paracellular permeability by modulating the expression of those cell junction genes. RNA and protein were extracted from Caco-2 cells treated with different concentrations of simotinib (0, 0.005, 0.02, 0.1, 0.5, 2.0 µM).…”
Section: Resultsmentioning
confidence: 99%
“…Reducing expression of cell junction genes led to increased paracellular permeability. A previous study reported that several cell junction genes were modulated by EGF, 15) so we tested whether simotinib increased the paracellular permeability by modulating the expression of those cell junction genes. RNA and protein were extracted from Caco-2 cells treated with different concentrations of simotinib (0, 0.005, 0.02, 0.1, 0.5, 2.0 µM).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to TGF-β, the extracellular stimulus EGF is also known as a strong enhancer of epithelial cell restitution [24], [33], [34] and triggers the ERK1/2/MAPK pathway, which is linked to cell migration and proliferation. Thus, the migration properties of IEC-6 cells in the presence or absence of exogenously added EGF and PD98059, a selective inhibitor of MEK1 phosphorylation upstream of ERK1/2, were examined, to see if Dex or the SEGRAs CpdA and ZK216348 modulate intestinal epithelial migration by this pathway.…”
Section: Resultsmentioning
confidence: 99%
“…With respect to mucosal healing, one of the regulatory peptides, EGF, likewise a strong enhancer of epithelial cell restitution [24], [33], [34], and its signalling via the EGF/ERK1/2/MAPK pathway, are of particular interest, as its downstream targets are involved in cellular events such as cell motility and proliferation [28], [44], and the influence of GCs upon the EGF/ERK1/2/MAPK pathway is also well documented [45], [46]. Indeed, addition of exogenous EGF in combination with Dex led to a complete restoration of the Dex-mediated decrease of restitution in the utilised in vitro wound healing model.…”
Section: Discussionmentioning
confidence: 99%
“…The cDNA was also checked for contaminating chromosomal DNA by amplification of a promoter sequence from the β-actin gene. The specific primer pairs used in this study are listed in Table 1 or have been published previously [20,21]. …”
Section: Methodsmentioning
confidence: 99%